뇌성마비아동의 초조기치료 지연요인에 관한 연구 - 장기연 (연세대학교 보건대학원, 1987)
[한글] 본 연구의 목적은 우리나라 뇌성마비아동의 재활치료 실태를 파악하고, 초조기치료의 지연과 관련된 요인을 알아 보는데 있다. 조사대상은 1987년 4월 20일부터 4월 30일까지 서울특별시에 소재한 뇌성마비아동을 치료하는 기관에서 무작위로 6개 기관을 표본추출한 후 그 기관에서 치료중인 뇌성마비아동의 어머니 225명으로 하였고, 조사도구로는 설문지를 사용하였다. 초조기치료의 지연과 관련된 요인을 알아보고자, 조사대상을 초조기치료군과 초조기치료지연군으로 나누어 여러 변수와의 관계를 비교분석 하였다. 본 연구의 결과는 다음과 같다. 첫째, 재활치료 시작시기는 출생시∼12개월이 74명 (32.9%), 13∼24개월이 60명 (26.7%), 3세 이후가 57명 (25.3%), 36개월이 33명 (14.7%)의 순으로 3분의 2의 아동이 초조기치료 시기를 놓치고 있었다. 둘째, 초조기치료군과 초조기치료지연군간의 이상발견시기 (P<0.001) 및 뇌성마비로 진단된 시기 ( P<0.001), 진단명 (P<0.05), 치료권유 (P<0.05), 뇌성마비에 대한 지식정도 (P<0.05), 장애정도 (P<0.001)는 유의한 관련이 있어 초조기치료시행에 영향을 주었다고 볼 수 있었다. 세째, 초조기치료군과 초조기치료지연군간의 교육수준(P>0.05), 가정경제수준 (P>0.05), 치료협조 여부 (P>0.05), 의료기관 접근용이정 (P>0.05)은 유의하지 않아 초조기치료시행과 관련이 없었다. 이상의 결과에서 보는 바와 같이 뇌성마비아동의 초조기치료는 잘 시행되고 있지 않으며, 초조기치료시행에 영향을 주는 요인으로는 이상발견시기 및 뇌성마비로 진단된 시기, 진단명, 치료권유, 뇌성마비에 대한 지식정도, 장애정도 등을 들 수 있었다. 따라서 본 연구에서 밝혀진 요인들을 근거로 하여 뇌성마비아동의 재활치료 효과를 높히기 위해서, 뇌성마비의 위험성이 있는 아동의 추적검사 프로그램, 뇌성마비의 초조기치료의 중요성에 대한 적극적인 홍보 등 종합적인 대책이 강구되어야 할 것으로 생각된다. [영문] The purpose of this study was to Survey the rehabilitative treatment status of cerebral palsied children and investigate factors delaying their very early treatment. The subjects were 225 mothers of cerebral palsied children who were treated at six facilities in Seoul. Selection was by random sampling. Data was obtained from April 20, 1987 to April 30, 1987 by means of a questionnaire. To investigate factors delaying very early treatment, subjects were divided to a very early treatment group and a delayed very early treatment group. The results were as follows : 1. Of a total of 225, 12 children (32.9%) began to receive rehabilitative treatment during the period berth - 12 months, 60 children (26.7%) between 13 - 24 months, 57 children (25.3%) after 3 years of age and 33 children (14.9%) between 25 - 36 months of age. Therefore 2/3 of the studs group of cerebral palsied children missed the opportunity for very early treatment. 2. In comparing the age of the Child at the time to discover developmental disturbance (P<0.001), the age of the child at the time of diagnosis (P<0.001), the first diagnosis (P<0.05), referral to treatment (P<0.001), knowledge of cerebral palsy (P<0.05) and degree of handicap (P<0.001), differences between the very early treatment group and the delayed very early treatment group were significant. Therefore, these factors were considered to have an influence on the implementation of very early treatment. 3. There was no significant difference between the delayed and non-delayed groups for education level (P>0.05), home economic level (P>0.05), family's cooperation with treatment (P>0.05) and accessibility of facility (P>0.05). These results suggest that significant factors effecting a delay tn starting very early treatment of cerebral palsied children were the age of the child at the time to discover developmental disturbance, the age of the child at the time of diagnosis, the first diagnosis, referral to treatment, knowledge of cerebral palsy and degree of handicap. Based on the results of this study, a comprehensive plan should be developed to promote the very early treatment of infants with cerebral palsy. This plan should incorporate early examination of infants-at-risk for cerebral palsy, and public information on cerebral palsy, and the results of rehabilitation management programs.
보건학과/석사